Pengaruh Profitabilitas, Likuiditas, Struktur Modal, dan Pertumbuhan Laba terhadap Kualitas Laba - Farah Diffa Gusti Aprissa; Putri, Intan Lifinda Ayuning (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aimed to empirically examine the influence of profitability, liquidity, capital structure, and earnings growth on earnings quality in non-cyclical consumer sector businesses listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. This study employs a quantitative technique based on secondary data obtained from yearly financial reports available on the official website www.idx.co.id. A purposive sampling approach was employed to choose the sample, yielding 54 observations. Data was analysed using multiple linear regression approaches and IBM SPSS Statistics software version 26. The results of this study show that liquidity positively and significantly influences on earnings quality. In contrast, profitability and capital structure have a strong negative impact on earnings quality. Furthermore, the profits growth variable shows no substantial impact on earnings quality.